1996
DOI: 10.1016/0306-3623(95)02010-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flavonoids on rat aortic smooth muscle contractility: Structure-activity relationships

Abstract: ABSTRACT. 1. Flavonoidsproducedaconcentration.dependentrelaxationofthecontractileresponses induced by noradrenaline, KCI, or phorbo112-myristate-13-acetate in rat aortic rings. Only the flavonoid with three contiguous hydroxyls in B rings (myricetin), at low concentrations, potentiates the contractions evoked by these agonists.2. The relaxant effects of flavanone on the noradrenaline-induced contractions were potentiated by isoprenaline and those of morin, chrysin, flavanone, and naringenin by sodium nitroprus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
86
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 20 publications
9
86
1
3
Order By: Relevance
“…21) For example, CA is a water-soluble antioxidant. [21][22][23] MO is a lipid-soluble antioxidant but it is weak, and a very wide range of biological actions of MO, including inhibitory activity against, oxidative modification of low-density lipoprotein 22) and a vasorelaxant effect, 23) have been reported. trans-RV in plasma is very sparse and shows a short half-life (8-14 min) because of its poor water-solubility and instability, as it converts to a cis form (a less active form).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21) For example, CA is a water-soluble antioxidant. [21][22][23] MO is a lipid-soluble antioxidant but it is weak, and a very wide range of biological actions of MO, including inhibitory activity against, oxidative modification of low-density lipoprotein 22) and a vasorelaxant effect, 23) have been reported. trans-RV in plasma is very sparse and shows a short half-life (8-14 min) because of its poor water-solubility and instability, as it converts to a cis form (a less active form).…”
Section: Discussionmentioning
confidence: 99%
“…CA is a widely distributed phenolic acid present in coffee and some fruits, and it is known as a water-soluble antioxidant, and it has been successfully encapsulated in low-cost, high-volume yeast cells for the first time. [20][21][22][23] MO is a flavonoid found in figs and other Moraceae, which are used as herbal medicines, and it is known as a major lipid-soluble antioxidant. [22][23][24] RV is a naturally occurring polyphenolic phytoalexin found in many plants and contained in foods and drinks such as in Mediterranean diets and French wine, and it is known as a poor water-soluble antioxidant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in our laboratories and elsewhere have shown that quercetin, kaempherol, morin, myricetin, luteolin and rutin, all present in PGE, possess vasodilator effects in rat isolated aorta and porcine coronary artery (Duarte et al, 1993a, b;Herrera et al, 1996;Perez-Vizcaíno et al, 2002;Ajay et al, 2003;Xu et al, 2007). In the present study, we report for the first time in biomedical literature, that Psidium guajava crude leaf aqueous extract, which contains many flavonoids, especially quercetin, induces vascular smooth muscle relaxation, with potency lower than that of pure quercetin (Chiwororo and Ojewole, 2008 -unpublished observation).…”
Section: Discussionmentioning
confidence: 93%
“…Myriecetin showed contractile and myorelaxant effects if used in low doses and high doses, respectively. (Herrera et al, 1996). Possibly the contractile effect of quercetin and luteolin used in low doses was missed by some authors who studied the effect of those flavonoids on smooth muscle contractility only in the range of doses 1 to 100 μM (Capasso et al, 1991a and1991b;Hammad and Abdalla, 1997; Amira et al, 2008).…”
mentioning
confidence: 99%